Gambaran Tingkat Kecemasan Perawat Pada Masa Pandemi COVID - 19 di Puskesmas Tembuku I & II Kabupaten Bangli - I Komang Jarna; NLPS Yudhawati (Bali Health Published Journal, 2023)
Background: The COVID-19 pandemic has caused a lot of anxiety, chaos and mental disorders when the COVID-19 cases in Bali as of 23 November 2020 recorded 13,331 positive cases with details of 762 active cases, 12,155 people recovered and 414 people died.  In Tembuku sub-district was recorded 170 positive cases which resulted in health workers getting more depressed and worried because of the workload, they must remember the complete PPE (Personal Protective Equipment) every time they serve patients.  In addition, the fear of infection and infection triggers a psychological problem that is detrimental and has a detrimental effect. Methods: This study used a descriptive method with a quantitative approach by using a measuring instrument in the form of a DASS 14 questionnaire. The population in this study was 32 respondents .  The sampling technique used was total sampling. Results: The results of this research showed the most respondents were female with a total of 72%, the age category was dominated by the age of 26-35 years, 63% probability, the highest education was DIII with 84%.  The highest count rate was the severe level at 43%. Conclusion: Most respondents experienced anxiety during the COVID-19 pandemic. The recommendation of this research is Government can provide moral emotional support to nurses so that they can increase self-confidence.